2012
DOI: 10.1001/archsurg.2012.77
|View full text |Cite|
|
Sign up to set email alerts
|

Risk Factors for Anastomotic Leak and Mortality in Diabetic Patients Undergoing Colectomy

Abstract: To determine the risk factors in diabetic patients that are associated with increased postcolectomy mortality and anastomotic leak. Design: A prospectively acquired statewide database of patients who underwent colectomy was reviewed. Primary risk factors were diabetes mellitus, hyperglycemia (glucose level Ն140 mg/dL), steroid use, and emergency surgery. Categorical analysis, univariate logistic regression, and multivariate regression were used to evaluate the effects of these risk factors on outcomes. Setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
3
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 22 publications
0
35
3
2
Order By: Relevance
“…A study of US veterans that assessed 30‐day mortality following surgery for CRC showed that patients with preexisting DM had a significantly increased risk of developing AL . Other studies were unable to show an increased risk of AL among patients with DM and CRC . In our study DM was not found to be a risk factor for AL, and patients with diabetes were not more likely to have a permanent stoma than non‐DM patients.…”
Section: Discussioncontrasting
confidence: 70%
“…A study of US veterans that assessed 30‐day mortality following surgery for CRC showed that patients with preexisting DM had a significantly increased risk of developing AL . Other studies were unable to show an increased risk of AL among patients with DM and CRC . In our study DM was not found to be a risk factor for AL, and patients with diabetes were not more likely to have a permanent stoma than non‐DM patients.…”
Section: Discussioncontrasting
confidence: 70%
“…A large statewide collaborative study of 5123 patients evaluated the anastomotic leakage rate and mortality after colectomy in diabetic patients. Although diabetes did not appear to be a risk factor for anastomotic leakage, diabetic patients who had leakage had a four‐fold higher mortality than nondiabetic patients . Even though diabetes was not associated with pouch failure in our study, pouch survival rates were considerably decreased in patients who had anastomotic leakage.…”
Section: Discussioncontrasting
confidence: 67%
“…An exception was the study of Ziegler et al . , which included 5123 patients, 214 of whom were treated with steroids. Ziegler et al .…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, corticosteroids have been linked to numerous, and sometimes severe, complications. Although corticosteroids are known to impair wound healing, their influence on the healing of colorectal anastomoses remains unclear and studies have reported conflicting results [6,[8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%